2013
DOI: 10.1021/bm400634j
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Hydrogels with Enhanced Initial and Sustained Cell Interactions

Abstract: The highly tunable properties of poly(ethylene glycol) (PEG)-based hydrogel systems permit their use in a wide array of regenerative medicine and drug delivery applications. One of the most valuable properties of PEG hydrogels is their intrinsic resistance to protein adsorption and cell adhesion, as it allows for a controlled introduction of desired bioactive factors including proteins, peptides, and drugs. Acrylate-PEG-N-hydroxysuccinimide (Acr-PEG-NHS) is widely utilized as a PEG linker to functionalize bioa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 41 publications
(117 reference statements)
0
29
0
Order By: Relevance
“…Additionally, PEGDAA hydrogels containing acrylate-PEG-functionalized collagen or Scl2 (1X) were incubated at 37°C in PBS for 6 weeks with no differences in bioactivity compared to 1 day swelling. 59 These results indicate that the proteins are not denaturing in the timeframe of this study and that losses in bioactivity can solely be attributed to hydrolytic degradation of the protein linker.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Additionally, PEGDAA hydrogels containing acrylate-PEG-functionalized collagen or Scl2 (1X) were incubated at 37°C in PBS for 6 weeks with no differences in bioactivity compared to 1 day swelling. 59 These results indicate that the proteins are not denaturing in the timeframe of this study and that losses in bioactivity can solely be attributed to hydrolytic degradation of the protein linker.…”
Section: Discussionmentioning
confidence: 67%
“…Therefore, the reduction in bioactivity was attributed to degradation of the protein linker. In a related study, a significant reduction in protein retention was found on 0.5X Acr-PEG-functionalized collagen and Scl2 PEGDAA hydrogels after 6 weeks of swelling in PBS 59 . The reduction in protein retention led to corollary decreases in spreading for collagen and reduced adhesion and spreading for Scl2-2.…”
Section: Discussionmentioning
confidence: 81%
“…However, for any ‘off the shelf’ product, sterilization and storage conditions are important. Recent studies have shown that dry storage of these modified materials is better than wet storage (Luong et al 2013), as under wet conditions, ester hydrolysis of the protein linker has been attributed to the slow loss of the bioactive collagen component (Luong et al 2013, Browning et al 2013). However, this problem can be potentially resolved through use of an alternative modification reagent, acrylamide-PEG-isosyanate (Browning et al 2013).…”
Section: Products and Applicationsmentioning
confidence: 99%
“…For example, the properties of collagen hydrogels were altered by cross-linking the protein-based hydrogel with multi-armed poly(ethylene glycol) (PEG) stars containing activated esters on the termini that reacted with amine residues on the protein [23]. PEG is an ideal candidate to add to protein hydrogels because it is biocompatible and inert [2, 33], and therefore the biochemical cues in the hydrogel remain the same. Herein, we demonstrate a new approach to tissue specific ECM-based hydrogels for tissue engineering by synthesizing myocardial matrix-PEG hybrid hydrogels by two different methods.…”
Section: Introductionmentioning
confidence: 99%